Informal Agenda Setting - van Keulen, Ira; Korthagen, Iris (European E-Democracy in Practice, 2020)
In this chapter, Van Keulen and Korthagen describe two tools which are used by citizens to put issues they think are important on the political agenda: the Dutch website petities.nl and the Finnish Avoin Ministeriö (Open Ministry) which ceased to exist but was aimed to help citizens’ initiatives such as submitting a bill. Both are organised bottom-up. In their description and analysis of both cases, the authors put a strong focus on the participatory process and practical experiences of users. For a better understanding of these tools and how they are used in practice, interviews were conducted with the founders and researchers familiar with both tools. Strengths and weaknesses are identified and possibilities for improvements explored. While both tools show positive results in different ways, their impact in terms of policy tools leaves much to be desired. Interestingly, the low impact does not seem to create too much disillusionment among the participants. Quite the opposite, the amount of visitors of petities.nl have been steadily increasing. And participants of the Open Ministry are willing to accept not achieving the desired outcome, as long as they perceive the process to be fair. It turns out that e-participation tools are more often a successful civic instrument, but not a convincing policy instrument.